Oxygen Evolution: FeN4 Sites Embedded into Carbon Nanofiber Integrated with Electrochemically Exfoliated Graphene for Oxygen Evolution in Acidic Medium (Adv. Energy Mater. 26/2018). Issue 26 (14th September 2018) - Lei, Chaojun; Chen, Hengquan; Cao, Junhui; Yang, Jian; Qiu, Ming; Xia, Ying; Yuan, Chris; Yang, Bin; Li, Zhongjian; Zhang, Xingwang; Lei, Lecheng; Abbott, Janel; et al.
Abstract : In article number1801912, Ming Qiu, Gang Wu, Qinggang He, Yang Hou, and co‐workers report the synthesis of atomically dispersed iron‐nitrogen coordinated carbon fiber grown on electrochemically exfoliated graphene, which demonstrates excellent electrocatalytic oxidation evolution from water splitting in acid. The outstanding performance is attributed to the highly active sites of the Fe‐N4 species.